Impact of bacterial volatiles on phytopathogenic fungi: an in vitro study on microbial competition and interaction. (29th October 2021) - Das, Piyali; Effmert, Uta; Baermann, Gunnar; Quella, Manuel; Piechulla, Birgit
Abstract: Microorganisms in the rhizosphere are abundant and exist in very high taxonomic diversity. The major players are bacteria and fungi, and bacteria have evolved many strategies to prevail over fungi, among them harmful enzyme activities and noxious secondary metabolites. Interactions between plant growth promoting rhizobacteria and phytopathogenic fungi are potentially valuable since the plant would benefit from fungal growth repression. In this respect, the role of volatile bacterial metabolites in fungistasis has been demonstrated, but the mechanisms of action are less understood. We used three phytopathogenic fungal species ( Sclerotinia sclerotiorum, Rhizoctonia solani, and Juxtiphoma eupyrena ) as well as one non-phytopathogenic species ( Neurospora crassa ) and the plant growth promoting rhizobacterium Serratia plymuthica 4Rx13 in co-cultivation assays to investigate the influence of bacterial volatile metabolites on fungi on a cellular level. As a response to the treatment, we found elevated lipid peroxidation, which indirectly reflected the loss of fungal cell membrane integrity. An increase in superoxide dismutase, catalase, and laccase activities indicated oxidative stress. Acclimation to these adverse growth conditions completely restored fungal growth. One of the bioactive bacterial volatile compounds seemed to be ammonia, which was a component of the bacterial volatile mixture. Applied as a single compound in biogenic concentrations ammonia also caused an increase in lipid peroxidation and enzyme activities, but the extent and pattern did not fully match the effect of the entire bacterial volatile mixture. Abstract : Bacterial volatiles caused fungal growth retardation and elicited an oxidative stress response. Effects were transient as defense mechanisms allowed acclimation to adversely affect growth conditions and the fungus resumed hyphal growth.